Level of Participation of Salassae Rural Swabina Community - Arizal Arizal Mangka; Syahdar Baba; Andi Amidah Amrawati (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2019)
Natural farming is an agricultural system that does not use external inputs in the implementation of its farming. This study aims to determine the level of participation of farmers at each stage of planning and decision making, evaluation and utilization of results. The research method uses a qualitative case study method. Data collection uses the method of triangulation methods, namely in-depth interviews, observation and focus group discussions. Key informants included the SRSC founder, chairman, active members and new members. The results showed the level of participation of farmers at the planning stage is at the level of self-participation where farmers decide themselves willingness to participate in natural farming activities. In addition, farmers plan their farming according to the resources they have and are guided by SRSC instructors. At the implementation stage, farmers carry out natural farming independently and are guided by extension workers or other farmers who have already done natural farming first. At the evaluation stage, the farmer evaluates every activity that has been carried out. Evaluation is not only at the end of the activity, but at the time of the activity, the farmer also conducts an evaluation together with more advanced farmers. At the yield utilization stage, farmers' income increases and the ability of farmers to do natural farming continues to increase as they become increasingly involved in activities in SRSC.